Estimation of nutrition status of school going children in the local area District Kohat, Pakistan - Ullah, Shakir; Saeed, Usman; Rahman, Muhannad Iqbal Khan; Ullah, Said; Islam, Umair; Gul, Muhammad Kashif; Khan, Yaseen; Bibi, Maryam; Ali, Basit (Food, Agriculture and Natural Resources - NETWORKS, 2024)
There are many determinants of malnutrition among school-going children. These include poverty, illiteracy and inadequate diet. To assess the nutritional status of primary and high school children in an urban area of Kohat. A cross-sectional study was performed in a primary and high school of Government sector in the rural area of Kohat. A total of 750 children between the ages of 4-15 years were studied. A total of 750 children between the ages of 4-15 were analyzed for this study. Out of 750 school-going students, 300(40%) were found positive, and 450(60%) were found normal according to age. Gender-wise analysis shows that in male students 105 were found positive for stunting and 75 male students were underweight. In overall female students, 69 were found stunting and 51 were found underweight. According to the age group between 4 to 10 years 45 female students were found stunting and 30 were found underweight. While in the age of 11 to 15 years 24 students were stunting and 21 students were underweight. Gender wise prevalence of stunted and underweight showed more boys than girls. A lot more efforts are required in economic, educational, and media to improve the nutritional condition of the new generation of Kohat, Pakistan.